Identification of Calpain 10 Isoforms (b, d, e, f & h) Conserved Regions and Possible Functional Prophecy through Bioinformatics - Kausar Saboohi,; Samina Bano ,; Bushra Chaudhry, (Journal of Basic & Applied Sciences, 2013)
Calpain 10 is an atypical calpain ubiquitously exist in all human tissues. It exhibits eight protein isoforms designated as “a-h” which play a vital role in glucose homeostasis but actual mechanism of action is yet to be ascertained. We have predicted the partial roles of Isoform a, c and g previously. They were envisaged to act partially as mu and m-calpain cysteine proteases. Here we predict the function of minor isoforms b, d, e, f and h. We have applied NCBI Blast and Conserved domain tool for nucleotide and protein alignments. Blast query indicated 87%, 84%, 87%, 94% and 34% identity of isoform b, d, e, f and h with canonical sequence of calpain 10 a isoform. Conserved domain analyses of protein sequences revealed significant structural similarities of their N-terminal domain I and II with catalytic domain of cysteine protease superfamily PC1 (e-value:CAPN10b, d, e = 2.41e-76, CAPN10f = 1.07e-43 and CAPN10h = 1.13e-17). Isoform b, d and e have one consecutive domain similar with C2 like subdomain III (e-value=2.92-32, 1.03e-35, 1.88e-14 respectively) and was classified in CAPN10 group of Palb subfamily. Isoform f and h were lacking this domain and had shorter sequences. Although structural similarities are not guaranteed for similar actions but domain homology predicted the existence of similar functions as of calpain I and II.